Subjects of disciplinary proceedings against a judge under the legislation of Ukraine and Spain: comparative legal analysis - L. G. Bzova (Аналітично-порівняльне правознавство)
Disciplinary liability of judges is one of the key mechanisms of holding judges accountable. States are called upon to regulate this area, balancing two main interests – the need to ensure functional mechanisms of judicial accountability and to ensure real independence of judges. The main international legal instruments on the disciplinary liability of judges stipulate that states shall provide clear rules for which judges may be disciplined, excluding disciplinary liability for minor offences and for the interpretation of laws and facts. Disciplinary proceedings should either be conducted by an independent body. A proper disciplinary mechanism that holds all public officials accountable for misconduct is an important element of a credible justice system. At the same time, judicial discipline must be carefully balanced with the principle of judicial independence as a cornerstone of the rule of law. A miscarriage of justice that harms fundamental human rights and freedoms is not sufficient to hold a judge accountable. It must be attributed to the judge as a result of his or her performance of his or her functions in bad faith or through gross negligence.